Novel prodrug-inspired eugenol derivatives with enhanced bioavailability, anti-diabetic and anti-glycation efficacies - Kataria, Priyanka; Vairale, Shiva; Mote, Chandrashekhar; Joshi, Kaustubh; Joshi, Rakesh; Kulkarni, Mahesh J.; Giri, Ashok P.; Kontham, Ravindar; Agawane, Sachin B. (Journal of Molecular Structure, 2026)
In this study, we present the design, synthesis, and evaluation of novel eugenol analogs aimed to overcome its limited bioavailability due to insolubility in aqueous media. Thus, we re-engineered eugenol using prodruginspired structural modifications to improve pharmacokinetic properties. First, we structurally modified eugenol and synthesized its natural amino acid conjugates as esters and carbamates. These were prepared in NBoc protected, free amine, and HCl salt forms. These modifications are expected to improve the polarity and solubility of eugenol congeners in biological systems. They can also release the parent eugenol through enzymatic hydrolysis, enhancing its therapeutic potential. Next, we comprehensively screened for these derivatives through in silico studies followed by in vitro and in vivo assays. These include DPPH radical scavenging (IC50 range: 37.7 to 103.7 mu M), inhibition of (i) alpha-amylase (IC50 23.1 to 67.3 mu M), (ii) alpha-glucosidase (IC50 43.6 to 50.4 mu M), (iii) glycation (IC50 31.9 to 110.3 mu M) along with pharmacokinetic profiling and toxicity assessments. These experiments collectively demonstrated improved activity of eugenol analogs for several important parameters. Specifically, six analogs-epoxy eugenol (39), hydroxy eugenol (43), aspartate eugenol (26), isoleucinate eugenol (24), glutamate eugenol (37), and glutamate-salt eugenol (27) exhibited superior bioavailability, absorption, and distribution over to the parent compound eugenol. These analogs were found to be non-toxic and safe for oral administration. Overall, the study establishes a mechanistic and rational framework for modifying eugenol to overcome its inherent biopharmaceutical limitations, positioning them as promising candidates for treating diabetes and glycation-related conditions.
Keywords: Amino acid conjugates; Antidiabetic activity; Bioavailability enhancement; Drug design and synthesis; Eugenol analogs; In silico and in vitro studies